Fission Yeast Sap1 Protein Is Essential for Chromosome Stability - de Lahondès, Raynald (American Society for Microbiology, 2003)
Sap1 is a dimeric sequence-specific DNA binding-protein, initially identified for its role in mating-type switching of the fission yeast Schizosaccharomyces pombe. The protein is relatively abundant, around 10,000 dimers/cell, and is localized in the nucleus. sap1(+) is essential for viability, and transient overexpression is accompanied by rapid cell death, without an apparent checkpoint response and independently of mating-type switching. Time lapse video microscopy of living cells revealed that the loss of viability is accompanied by abnormal mitosis and chromosome fragmentation. Overexpression of the C terminus of Sap1 induces minichromosome loss associated with the “cut” phenotype (uncoupling mitosis and cytokinesis). These phenotypes are favored when the C terminus of Sap1 is overexpressed during DNA replication. Fluorescence in situ hybridization experiments demonstrated that the cut phenotype is related to precocious centromere separation, a typical marker for loss of cohesion. We propose that Sap1 is an architectural chromatin-associated protein, required for chromosome organization.